1995
DOI: 10.1107/s0907444994007158
|View full text |Cite
|
Sign up to set email alerts
|

Time-averaging crystallographic refinement: possibilities and limitations using α-cyclodextrin as a test system

Abstract: The method of time-averaging crystallographic refinement is assessed using a small molecule, a-cyclodextrin, as a test system. A total of 16 refinements are performed on simulated data. Three resolution ranges of the data are used, the memory relaxation time of the averaging is varied, and several overall temperature factors are used. The most critical factor in the reliable application of timeaveraging is the resolution of the data. The ratio of data to molecular degrees of freedom should be large enough to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
4

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 6 publications
0
24
0
4
Order By: Relevance
“…Using linear regression for residues 5 to 55, we found the following correlation coefficient values: 0.35 (4PTI versus 5PTI); 0.22 (4PTI versus 6PTI); and 0.64 (5PTI versus 6PTI). Recently, it has been shown by comparison of electron-density maps obtained from anisotropic B-factor refinement and from time-averaging MD refinement using exact data that the former technique yields a worse representation of the exact data than the latter (Schiffer et al, 1995). The influence of the force field (reason (4)) is difficult to assess but should not be underestimated.…”
Section: Simulated B-factors Calculated Using Averaging Windows Of DImentioning
confidence: 99%
“…Using linear regression for residues 5 to 55, we found the following correlation coefficient values: 0.35 (4PTI versus 5PTI); 0.22 (4PTI versus 6PTI); and 0.64 (5PTI versus 6PTI). Recently, it has been shown by comparison of electron-density maps obtained from anisotropic B-factor refinement and from time-averaging MD refinement using exact data that the former technique yields a worse representation of the exact data than the latter (Schiffer et al, 1995). The influence of the force field (reason (4)) is difficult to assess but should not be underestimated.…”
Section: Simulated B-factors Calculated Using Averaging Windows Of DImentioning
confidence: 99%
“…This method introduced by Torda et al (1989) and implemented in macromolecular crystallography by Gros et al (1990), showed a reduction in R -value. However, cross-validation introduced subsequently (Brünger, 1992) revealed chronically over-fitted models (Burling and Brunger, 1994; Clarage and Phillips, 1994; Schiffer et al, 1995). …”
Section: Introductionmentioning
confidence: 99%
“…Experimentally derived boundary conditions are used to explicitly enforce agreement between a simulation and some experimental result. These may be applied to enforce, e.g., the reproduction of (average) electron density maps from X-ray crystallography [27,28,29,30], or the agreement with (average) interatomic distances and J-coupling constants from NMR measurements [31,32,33,30].…”
Section: Introductionmentioning
confidence: 99%